Preparation of the Arabic language teacher in the light of the ompetencies (a theoretical view) of e-learning (Journal of the College of Basic Education, 2022)
The current research aims to identify the level of spelling achievement among students of the first grade teacher department in the College of Basic Education at Al-Mustansiriya University.To achieve the goal of the research, the researcher added the following two questions:1.What is the level of the degree of spelling achievement among students of the teacher’s department in the first grades in the College of Basic Education / Al-Mustansiriya University?Are there statistically significant differences in the level of spelling achievement among the students of the first grades teacher's department due to the gender variable?The research sample amounted to (97) male and female students from the first stage in the first grade teacher’s department in the College of Basic Education / Al-Mustansiriya University, with (43) male and (54) female students.The researcher prepared an achievement test consisting of (60) multiple-choice items, and after extracting its apparent validity, it was applied to an exploratory sample to measure the level of difficulty, discriminatory power, and effectiveness of alternatives, then find its stability. After processing it statistically using the following T-Test:1.Weakness of the level of spelling achievement among the students of the first grades teacher section, as the average score of students in the achievement test was (27%), which is less than the minimum passing score (50%), which is equivalent to the hypothetical average of the test (30%) .2.There is no difference in evaluating the level of the weak and the acceptable level between the male and female students of the research sample at the level of significance (0.05).There is a difference in evaluating the average level between the male and female students of the research sample at the level of significance (0.05) and in the interest of the female students.4.As for the estimation of the good, it was obtained by three students from the research sample, and no student from the same sample obtained it, while no values ​​appeared in the test correction and the level of very good and the level of excellence for any of the students of the research sample.In light of the research results, the researcher reached several conclusions and made recommendations and suggestions